The Surface Modification of Ag3PO4 using Tetrachloroaurate(III) and Metallic Au for Enhanced Photocatalytic Activity - Uyi Sulaeman; Richo Dwi Permadi; Alfa Marcorius; Hartiwi Diastuti; Anung Riapanitra; Shu Yin (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
The improvement of Ag3PO4 photocatalytic activity was successful by incorporating tetrachloroaurate(III) (AuCl4−) and metallic Au on the surface of Ag3PO4. The photocatalysts were synthesized using the coprecipitation and chemisorption method. Coprecipitation of Ag3PO4 was carried out under ethanol-water solution using the starting material of AgNO3 and Na2HPO4.12H2O. AuCl4− ion and metallic Au were incorporated on the surface of Ag3PO4 using a chemisorption method under auric acid solution. The photocatalysts were characterized using XRD, DRS, SEM, and XPS. The AuCl4− ion and metallic Au were simultaneously incorporated on the Ag3PO4 surface. The high photocatalytic activity might be caused by increasing the separation of hole and electron due to capturing photogenerated electrons by metallic Au and Au(III) as electron acceptors. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).